Genetic programming : 15th European Conference, EuroGP 2012, Málaga, Spain, April 11-13, 2012. Proceedings - Moraglio, Alberto (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 15th European Conference on Genetic Programming, EuroGP 2012, held in Málaga, Spain, in April 2012 co-located with the Evo* 2012 events. The 18 revised full papers presented together with 5 poster papers were carefully reviewed and selected from 46 submissions. The wide range of topics in this volume reflects the current state of research in the field, including different genres of GP (tree-based, grammar-based, Cartesian), theory, novel operators, and applications.